POTENSI DAN STRATEGI PENGEMBANGAN EKOWISATA DI SITU KEMUNING, KECAMATAN BOJONGGEDE, KABUPATEN BOGOR - Jaelani, Rijal; Satjapradja, Ombo; Muttaqin, Zainal (Jurnal Nusa Sylva, 2018)
Lake (situ) is one of the aquatic ecosystems that serves as a reservoir of water resources derived from rainwater and from stream flow. Kemuning lake is one of 94 situ in Bogor Regency that located in Sudi Mampir sub Village, Cimanggis Village, Bojonggede District. Kemuning lake potential consists of lake, duck-like rides, teak stands, stretch of weeds, the starfruit tunnel, birds chirping and fishes. The results of the calculation of ecotourism resource assessment shows that the starfruit tunnel occupies the highest potential sequence with a mean value of 5.0, while based on assessment assessors shown the potential that has the highest average value of the lake with an average value of 5.3. Development strategy based on SWOT analysis result shown that Kemuning Situ occupies SO strategy (strength opportunity) with internal factor value 1.53 and external factor value 1.05. In order to support the realization of the Bogor Regency government program which has the tagline "Cibinong City Front Situ" then made Site Plan Kemuning lake area.